2016
DOI: 10.1016/j.jfma.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms of inflammatory response genes and the risk of ovarian cancer

Abstract: NFKB1 and ICAM-1 polymorphisms could serve as useful ovarian cancer risk prediction biomarkers for the Chinese population, while the utility of PPARG and E-selectin polymorphisms as biomarkers requires further confirmation in independent ovarian cancer cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“… 41 conducted their research in two different places (eastern and southern china), which were treated as four individual comparisons. Therefore, a total of 42 studies from 36 articles were identified, including 43,000 subjects (18,222 cases and 24,778 controls) 8 10 13 19 20 21 22 23 24 25 26 27 28 29 30 32 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 . Of the 42 included studies, five studies involving 7,186 subjects reported on colorectal cancer (CRC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 41 conducted their research in two different places (eastern and southern china), which were treated as four individual comparisons. Therefore, a total of 42 studies from 36 articles were identified, including 43,000 subjects (18,222 cases and 24,778 controls) 8 10 13 19 20 21 22 23 24 25 26 27 28 29 30 32 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 . Of the 42 included studies, five studies involving 7,186 subjects reported on colorectal cancer (CRC).…”
Section: Resultsmentioning
confidence: 99%
“…The -94 ins/del ATTG (rs28362491) polymorphism that involves deletion of four nucleotides in the promoter region of NFKB1 gene consists of three genotypes: homozygote insertion or wild-type (WW), homozygote deletion or variant (DD), and heterozygous ins/del (DW) 7 18 . According to published data, several search groups have investigated the relationship between the polymorphism and cancers risk 7 10 19 20 21 22 23 24 25 26 27 . However, these results obtained remains inconsistent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have tested the association between different forms of cancer and functional variants of genes responsible for the inflammatory process [ 5 – 8 ], such as interleukin 1A ( IL1A ), interleukin 4 ( IL4 ), nuclear factor kappa B1 ( NFKB1 ) and protease-activated receptor 1 ( PAR1 ) [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Survival (Murray et al 2013) rs230532, rs3774932 Clinical outcome Ovarian cancer (Fan et al 2011, Huo et al 2013, Chen et al 2015a, Lu et al 2016 rs230528, rs230521, rs4648068, rs3774964, rs3774968, rs28362491…”
Section: Type Of Endocrine-related Malignancymentioning
confidence: 99%